Humor, Identitas, dan Keterlibatan: Dampak Meme Marketing dan Representasi Maskulinitas Merek terhadap Customer Engagement - Wardanu, Aditya Putra (IPM2KPE, 2025)
This study aims to analyze the influence of meme marketing and brand representation (masculinity) on customer engagement of followers of humor Instagram accounts in Indonesia. The research method used is a quantitative approach with descriptive and explanatory design. Data were collected by distributing questionnaires using a Likert scale to 206 respondents selected using purposive sampling techniques. Data analysis was carried out using the Partial Least Square (PLS) method with the help of WarpPLS 7.0 software. The results of the study indicate that both meme marketing and brand representation have a positive and significant effect on customer engagement. Specifically, meme marketing has a slightly stronger influence than brand representation. This finding confirms the importance of humor-based content strategies and masculine representations that are in accordance with the cultural identity of the target audience in increasing user engagement. The conclusion of this study is that the combination of meme marketing strategies and masculine brand representations synergistically creates strong and sustainable engagement on social media, especially Instagram. Keywords: Meme Marketing, Brand Representation, Brand Masculinity, Customer Engagement